1996
DOI: 10.1097/00000539-199606000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Vecuronium-Induced Depression of Phrenic Nerve Activity During Hypoxia in the Rabbit

Abstract: We investigated the effects of a close carotid injection of vecuronium on changes in phrenic nerve activity during different states of oxygenation. Experiments were performed on normothermic and mechanically ventilated adult New Zealand White rabbits with a tracheostomy under continuous thiopental infusion. Carotid arteries and carotid bodies were identified bilaterally followed by glomectomy on the contralateral side and positioning of a lingual artery catheter with its tip located in the carotid bifurcation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Our main result of a specific depression of HVR but not HCVR with partial neuromuscular blockade is consistent with previous work and as previously shown [8,9,[35][36][37][38]…”
Section: Discussionsupporting
confidence: 93%
“…Our main result of a specific depression of HVR but not HCVR with partial neuromuscular blockade is consistent with previous work and as previously shown [8,9,[35][36][37][38]…”
Section: Discussionsupporting
confidence: 93%
“…Hence, we think that there is sufficient information to answer the first issue raised by Dr Kopman and to support the opinion that even very low concentrations of a neuromuscular blocking agent (e.g. TOF ratios of 0.70) may markedly interfere with normal chemoreceptor oxygen sensing (1–7).…”
mentioning
confidence: 80%
“…In a series of human (1–3) and animal experiments (4, 5), we have demonstrated that neuromuscular blocking agents depress the hypoxic ventilatory response, mainly via an interaction with the oxygen‐sensing carotid body chemoreceptor. This depression is seen during a partial neuromuscular block and seems to follow the same time course of action as the classical neuromuscular block in skeletal muscle tissue.…”
mentioning
confidence: 99%
“…A possible pathway has been suggested by blocking the nicotinic ACh receptors on type I glomus cells in the rat [8]. In addition, Wyon and colleagues [9] demonstrated that hypoxia-induced phrenic nerve activities were partially blocked by arterial injection of vecuronium near the carotid body in the anesthetized rabbit. However, the importance of cholinergic signal transmission during hypoxia in the carotid body is still controversial.…”
mentioning
confidence: 99%